PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR MODAL DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN DI BEI - Siwalette, Jovanka Evangelia; Santioso, Linda (Jurnal Paradigma Akuntansi, 2025)
Thisiresearchiaims to to find affect of profitability, liquidity, capital structure and investmet decision affect firm ivalue, in ithe property & real iestate sector listed on the iIndonesia StockiExchange 2019-2021 period. The sample selection method used in this study was purposive sampling with 43 companies used as samples from 2019-2021. The data processed in this study used Microsoft Excel 365 and Eviews 12 and was processed using a multiple linear regression model. Theiresults of this study indicatei that profitability amd capital structure has no significant effect on firm value while liquidity and investment decision have a positive and significant effect on firm value. The iimplication iof thisiresearch isi theineed to improvei the ioperational management iof icompanies iby using internal funds and encouraging the role of managers wisely in making investment decisions that can increasei the ivalue of ithe company iwhich iwill provideia good signal foriinvestors.